The intolerance of tolerance - Carson, D. A. (Donald Arthur), 1946- (Michigan : Grand Rapids : William B. Eerdmans Publication company, 2012)
Carson traces the subtle but enormous shift in the way we have come to understand tolerance over recent years--from defending the rights of those who hold different beliefs to affirming all beliefs as equally valid and correct. He looks back at the history of this shift and discusses its implications for culture today, especially its bearing on democracy, discussions about good and evil, and Christian truth claims. --from publisher description
Introduction: the changing face of tolerance -- What is going on? -- Jottings on the history of tolerance -- Worse than inconsistency -- The church and Christian truth claims -- And still there is evil -- Tolerance, democracy, and majoritarianism -- Ways ahead: ten words
Includes bibliographical references and indexes
Keywords: Toleration -- Religious aspects -- Christianity; Religious tolerance -- Christianity; Christianity and other religions